Light alters the responses of two marine diatoms to increased warming. (February 2020) - Zeng, Xiaopeng; Jin, Peng; Jiang, Yingying; Yang, Haimei; Zhong, Jiahui; Liang, Zhe; Guo, Yingyan; Li, Peiyuan; Huang, Quanting; Pan, Jinmei; Lu, Hua; Wei, Yanyun; et al.
Abstract: In this study, we examined the effects of increased temperature (15, 20 and 25 °C) and different light levels (50, 200 μmol photons m −2 s −1 ) on two widely distributed diatoms, namely Phaeodactylum tricornutum and Thalassiosira weissflogii . Results showed that increasing light level counteracted the negative effects of high temperature on photosynthesis in both species, suggesting an antagonistic interaction between light and temperature. Contrary to the above results, light limitation diminished the temperature-sensitivity of carbonic anhydrase activity in two diatoms. We also observed species-specific responses of biomass, where increased temperature significantly decreased the biomass of P. tricornutum at both low and high light levels but showed no effects on T. weissflogii . Our study demonstrated that light can alter the physiological responses of diatoms to temperature but also revealed interspecific variations. We predict that in the future ocean with shallower upper mixed layer, T. weissflogii may be more competitive than P. tricornutum. Graphical abstract: Image 1 Highlights: Increasing light levels can counteract the negative effect of increasing temperature on photosynthesis in two diaoms . Light limitation diminishes the temperature-sensitivity of carbonic anhydrase activity in two diatoms. The biomass of P. tricornutum is more sensitive to temperature increase than T. weissflogii. Light can alter the physiological responses of diatoms to temperature, but showed interspecific variations. In the future ocean with shallower upper mixed layer, T. weissflogii may be more competitive than P. tricornutum.